Organosolv Pulping of Paraserianthes Falcataria - Bunye, Laura L. (1990)
The potential of organosolv pulping using Paraserianthes falcataria as a raw material was studied. organosolv pulping was carried out under 2 conditions of catalyst addition - 75% ethanol plus 0.05 M CaCl₂; and 75 % ethanol plus 0.10 M CaCI2; and without catalyst - 75 % ethanol only. The results indicated that without catalyst, organosolv pulping was incapable of reducing cooking chips into pulp. Catalyzed organosolv pulping at 0.05 M CaCl₂ produced pulp with screened yield of 45.31% and 46.67% for the 0.10 M CaCl₂ condition. These yields were slightly lower than the 48.56 % of kraft. The brightness of the unbleached pulps were 16.8 % and 15.9 % for organosolv pulping with 0.05 M and 0.10 M CaCl₂ conditions, respectively. These pulps were generally darker than the kraft pulp which had a brightness of 31.6 %. The strength properties i.e., burst, tear, tensile, stretch, and folding endurance of the two catalyzed organosolv pulps were very low compared to that of kraft pulp control. The total solids recovered from the black liquor of uncatalyzed organosolv process was 4.72 % while the catalyzed organosolv pulping were 7.0 % for 0.05 M CaCl₂ condition and 7.1 % for 0.10 M CaCl₂ condition.